Asia (Mongolia) - The Nature Conservancy (Symphony in the Flint Hills, 2015)
Mongolia is a country of vast landscapes and a small population. This article explains Mongolia’s grasslands, and the way of life of the nomadic peoples who sustain them, are threatened by mining, energy, and infrastructure development.
Keywords: Mongolia; introduction; grassland; people; habitat; ecosystem; animals; mamals; birds; camels; farming; livestock; ranching; ranchers; nomads; herders; sheppards; life